Systematic Literature Review Kekerasan dan Ujaran Kebencian di Media Online dan Televisi - Justitia Putra, Sandi; Faris, Faris (Calathu: Jurnal Ilmu Komunikasi, 2025)
This Systematic Literature Review method aims to examine the results of research related to how to analyze the content of violence and hate speech in online media. The 10 research papers used are considered eligible for analysis. In this paper, researchers include articles that examine hate speech and violence content in online media between 2019 and 2023. The studies reviewed provide exploratory data on the Internet and social media as a space for online violence and hate speech. Social media was originally intended to facilitate social interaction, fast communication, and personal networking, however, social media platforms that support this have become a breeding ground for violence, hate speech, radicalism and cyberbullying, a social threat. In this Systematic literature review, we can conclude that the types of online violence and hate speech found in social media studies are sexual violence and hate speech.